2023
DOI: 10.3390/curroncol30020155
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy and Chemotherapy Versus Sleep Disturbances for NSCLC Patients

Abstract: Introduction: Cancer patients are known to experience sleep disturbances that differ between disease stages and treatments. Regarding lung cancer patients and immunotherapy, information on their sleep disturbances has been recently acquired, but no comparison has been made between different treatment modalities. Patients and Methods: We recruited 98 non-small cell lung cancer patients; 49 had programmed death-ligand 1 expression of ≥50% and received immunotherapy as first-line treatment and 49 had programmed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…These symptoms improved quickly in patients with a PDL-1 expression greater than 80% during the first 4 months of treatment due to the rapid response of the tumor to immunotherapy. There was no difference in symptom control seen between patients who received nivolumab or pembrolizumab (85).…”
Section: Sleep Circadian Rhythms and Cancer Immunotherapy Sleep And I...mentioning
confidence: 80%
See 1 more Smart Citation
“…These symptoms improved quickly in patients with a PDL-1 expression greater than 80% during the first 4 months of treatment due to the rapid response of the tumor to immunotherapy. There was no difference in symptom control seen between patients who received nivolumab or pembrolizumab (85).…”
Section: Sleep Circadian Rhythms and Cancer Immunotherapy Sleep And I...mentioning
confidence: 80%
“…In contrast, in patients on standard chemotherapy, those with both partial response and stable disease continued to have sleep disturbances. They concluded that although ICIs did not induce sleep disturbance, treatment response may improve sleep disturbances ( 84 ). Another study by the same group showed that upon diagnosis, lung cancer patients had sleep disturbances including early morning awakenings, late sleep onset, prolonged nocturnal waking periods, daytime sleepiness, and unrefreshed sleep.…”
Section: Sleep Circadian Rhythms and Cancer Immunotherapymentioning
confidence: 99%
“…1 In this population, insomnia has been associated with psychiatric illness-partic-ularly anxiety and depressive disorders, 2 physical symptoms of pain or gastrointestinal symptoms, 3 or anticancer modalities such as chemotherapy, radiotherapy, and hormone therapy. 4 Additionally, multiple studies have suggested that poor sleep and disruption of the circadian rhythm can play a role in tumorigenesis and cancer progression that reinforces the reciprocal causative approach. 5 Based on the two-level model of arousal by Ong et al, 6 an individual's primary and secondary arousal influence their sleep disturbance.…”
Section: Introductionmentioning
confidence: 95%
“…Insomnia is a common condition among patients with cancer, with nearly half of patients with a recent cancer diagnosis suffering from insomnia symptoms [ 1 ]. In this population, insomnia has been associated with psychiatric illness—particularly anxiety and depressive disorders [ 2 ], physical symptoms of pain or gastrointestinal symptoms [ 3 ], or anticancer modalities such as chemotherapy, radiotherapy, and hormone therapy [ 4 ]. Additionally, multiple studies have suggested that poor sleep and disruption of the circadian rhythm can play a role in tumorigenesis and cancer progression that reinforces the reciprocal causative approach [ 5 ].…”
Section: Introductionmentioning
confidence: 99%